The Specialists’ Experience and Attttitude Towards the Elements of Music Therapy Methods in Social Work - Petrauskaitė-Dusevičienė, Rita; Jasiukevičiūtė, Toma (Socialinė teorija, empirija, politika ir praktika, 2014)
Summary The aim of the article is to present the results of a qualitative research – the specialists’ experience and attitude towards the music therapy practice in social work. Music therapy is making just the first steps in Lithuania, but its services are already integrated into healing, rehabilitation, recreation, care, special education, social work, preventive programmes. During the qualitative research, data analysis has revealed that the music therapy clients are persons of different age and gender, who have physical, psychological and/or social disorders and problems. If a social worker wants to use the elements of music therapy methods, the most important musical form in social work is integration into public through the cultural-artistic practice, while there are also developing clients’ social skills, communication, attention to others, responsibility, advertence, accumulation, the expression of negative and positive emotions. Key words: social work, the elements of music therapy methods